Augmented Reality Farm MAPPER Development: Lessons Learned from an App Designed to Improve Rural Emergency Response. Issue 3 (3rd July 2018) - Weichelt, Bryan; Yoder, Aaron; Bendixsen, Casper; Pilz, Matthew; Minor, Gerald; Keifer, Matthew
ABSTRACT: Fire departments have right-of-entry to most commercial industrial sites and preemptively map them to identify the onsite resources and hazards they need to promptly and safely respond to an emergency event. This is not the case for private farms. Emergency responders are blind to resources and hazards prior to arrival and must spend critical minutes locating them during an emergency response at a farm location. The original 2013 Farm Mapping to Assist, Protect and Prepare Emergency Responders (Farm MAPPER) project was undertaken to develop a method to give emergency responders an up-to-date view of on-farm hazard information to safely and efficiently conduct emergency response activities on private agricultural operations. In 2017, an augmented reality version of Farm MAPPER was developed to combine the technological advantages of geographic information system-based data points with a heads-up display and graphical overlay of superimposed hazard imagery and informative icons. The development and testing of this iOS- and Android-ready prototype uncovered lessons learned applicable to other mobile-based apps targeting farmers, ranchers, and rural populations faced with limited or inconsistent mobile internet connectivity.